Current therapy and novel agents for relapsed or refractory acute lymphoblastic leukemia. Issue 8 (August 2014) - Dinner, Shira; Lee, Daniel; Liedtke, Michaela
Abstract Despite high rates of complete remission in newly diagnosed adult acute lymphoblastic leukemia (ALL), rates of long-term leukemia-free survival are disappointingly low. Treatment of relapsed disease with chemotherapy, even in patients able to pursue consolidation with allogeneic stem cell transplant, has demonstrated limited success. There are no established standards of care in this setting and few standard treatment options. Novel agents targeting antigens on the lymphoblast cell surface offer unique side effect and anti-leukemic profiles which suggest that their use alone or in combination with chemotherapy may achieve improved outcomes for relapsed or refractory ALL.